Functional expression of a single-chain antibody fragment against human epidermal growth factor receptor 2 (HER2) in Escherichia coli - Akbari, V.; Sadeghi, H. M. M.; Jafrian-Dehkordi, A.; Abedi, D.; Chou, C. P. (Journal of Industrial Microbiology & Biotechnology, 2014)
The human epidermal growth factor receptor (HER) family plays an important role in cell growth and signaling and alteration of its function has been demonstrated in many different kinds of cancer. Receptor dimerization is necessary for the HER signal transduction pathway and tyrosine kinase activity. Recently, several monoclonal antibodies have been developed to directly interfere with ligand-HER receptor binding and receptor dimerization. A single chain variable fragment (ScFv) is a valuable alternative to an intact antibody. This report describes the production and purification of an ScFv specific for domain II of the HER2 receptor in Escherichia coli BL21 (DE3) cytoplasm. The majority of expressed of anti-her2his-ScFv protein was produced as inclusion bodies. A Ni-NTA affinity column was used to purify the anti-her2his-ScFv protein. The molecular weight of anti-her2his-ScFv protein was estimated to be approximately 27 kDa, as confirmed by SDS-PAGE and Western blotting assay. The anti-her2his-ScFv showed near 95 % purity and reached a yield of approximately 29 mg/l in flask fermentation. The purified anti-her2his-ScFv showed its biological activity by binding to HER2 receptor on the surface of BT-474 cells. This ScFv may be a potential pharmaceutical candidate for targeting tumour cells overexpressing HER2 receptor.